Dynamic heat transfer characteristics of gravity heat pipe with heat storage. (September 2022) - Zhang, Xuan; Wu, Suchen; Zhang, Chengbin; Chen, Yongping
Abstract: For the thermal performance enhancement of electronic components under intermittent high heat load, this paper proposes a gravity heat pipe with heat storage (GHPHS) that couples the advantages of GHPs and latent heat storage (LHS) units. A three-dimensional heat transfer model of GHPHS is developed and numerically studied, focusing on the comparison with traditional GHPs. Furthermore, the effects of the position and fin number of LHS units as well as the type and filling rate of phase change materials (PCMs) are investigated. The results indicate that the average heat source temperature reduces by 48.4 % and the maximum temperature duration shortens by 50 % with adding LHS units into GHPs, which can reduce the transient heat load shock and enhance the overall temperature uniformity. Moreover, the closer the LHS units is to heat sources, the better the temperature uniformity of GHPs is. When gallium is the PCM, the maximum heat source temperature reduces by 26 % when compared with the paraffin, and the increase in PCM fill rate facilitates a delay in the onset of maximum temperature and enhances the temperature uniformity. The fin number significantly affects the competition mechanisms between heat convection and conduction during the melting and solidification. As the fin number increases from 38 to 150, the maximum temperature of heat sources decreases by 29.7 % and the overall temperature uniformity of GHPs increases by 31.7 %. However, there is a limit to the influence of fin number on the thermal enhancement of GHPHSs. Highlights: Latent heat storage units are introduced to enhance temperature uniformity. A model of gravity heat pipe with heat storage is developed and verified. Temperature dynamic response and homogenization index variations are presented. Thermal enhancement methods concerning configurations of heat storage units are analyzed.